Public Financial Dependence on Algeria’s Hydrocarbon Exports Revenues (2000-2022) - Mourad Rahal; Hamma Amieur (Bulgarian Journal of International Economics and Politics)
This study explores hydrocarbon dependency in Algeria, focusing on oil price fluctuations’ impact on public finance and fiscal policies from 2000 to 2022. Despite efforts to diversify revenue sources, hydrocarbon revenues remain central to Algeria’s public finances. Energy market volatility introduces uncertainty, affecting budget stability and economic planning. Historical fuel price fluctuations have influenced fiscal policies, enabling development during high prices and necessitating austerity measures during declines. Using a Vector Autoregression (VAR) model, our analysis reveals a short-term influence of oil prices on fiscal expenditures. These findings underscore Algeria’s vulnerability to global oil market shocks, impacting developmental policies and economic restructuring. This research contributes to understanding economic diversification in oil-dependent economies, illuminating public finance dependency on hydrocarbon and its implications for fiscal stability in Algeria.